ANALYSIS OF MARKETING EFFICIENCY OF OYSTER MUSHROOM FARMING IN PULO RUNGKOM VILLAGE, DEWANTARA DISTRICT, NORTH ACEH REGENCY - Nadila Agustina; Rita Ariani Rita; Ade Firmansyah Tanjung Ade Firmansyah Tanjung (Jurnal Mahasiswa Agribisnis, 2026)
This study aims to analyze the marketing channels, marketing margins, farmers' share, and marketing efficiency of oyster mushrooms at the Indonesian Army's Arhanud TNI AD, managed by Mr. Dedi in Gampong Pulo Rungkom, Dewantara District, North Aceh Regency. The analysis methods used are marketing margin analysis, profit analysis, farmer share analysis, and marketing efficiency analysis. The results of the study show that there are two patterns of oyster mushroom marketing channels. Channel 1 and channel 2 are classified as efficient because their efficient values are below 50%, namely 1.43% and 32%, respectively. Keywords: Oyster Mushrooms, Marketing Channels, Marketing Efficiency